Music Composition Ngiyang | Komposisi Musik Ngiyang - I Gede Mekel Ekalawaya; I Nyoman Kariasa; I Wayan Diana (GHURNITA: Jurnal Seni Karawitan, 2022)
Ngiyang is a combination of two words that become one, namely ngibur and drifting. The purpose of this work is to explore further the composition of the new creation of gong kebyar percussion that has been designed by the stylist and how the stylist can grow something new in the form of this work as an experiment that the stylist does. This Ngiyang musical art work is created through a method that is carried out with a creative process that is always related to time, place, situation and condition of course balanced with the experience of the stylist in the world of Karawitan Art so as to achieve success in creating a work of art. The stage of creating Ngiyang's work was carried out with 36 musicians, using the medium of expressing gong kebyar. The results of this work are uploaded or broadcast on social media using the Youtube application with 14 minutes 41 seconds duration of the video.